AN ANALYSIS OF INTEGRATION OF BUSINESS CONTENT AND SKILLS IN ENGLISH FOR SPECIFIC ACADEMIC PURPOSES (ESAP) COURSE AT A HIGHER VOCATIONAL COLLEGE VIA CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) PERSPECTIVE - Qiao Li Ping; Norkhairi Ahmad (Universitas Duta Bangsa Surakarta, 2022)
Content and Language Integrated Learning (CLIL) theory emphasizes the mutually integrated and symbiotic relations between language and disciplinary knowledge. Based on this perspective, this study analyses the Double Focus teaching mode implementation that combined business knowledge with English language skills. This is implemented in a Business English course at higher vocational college to enable talent cultivation focus to shift to the internalization of business knowledge while continuing to improve English proficiency. The Double Focus teaching strategy adapted authentic business tasks simulation and practice from actual Foreign Reception Training Course like airport pick-up task via a plan, do, check, action (PDCA) approach. This study found that the integrative element promoted better association between language and business knowledge, raise awareness of using English in situational contexts and foster effective internalization of content knowledge among students. The successful implementation of such integrated CLIL can serve as a reference for the cultivation of language as well as business skills among undergraduates of English at higher vocational colleges